Monopelopia Fittkau, 1962 (Diptera: Chironomidae) from the Neotropical region: five new species, new records and updated keys - Dantas, Galileu P. S.; Hamada, Neusa (Zootaxa, 2017)
Five new species of Monopelopia from Brazil are described and illustrated, four of which are based on all life stages and one on adult male and pupa. The immature stages of Monopelopia edentata sp. nov. were collected in bromeliad phytotelmata, while the other species were collected associated with aquatic vegetation. New records for M. boliekae Beck & Beck and M. caraguata Mendes, Marcondes & Pinho are provided, as well as updated identification keys for males and immatures of the Nearctic and Neotropical Monopelopia species.